Assessment Tasks in Chemistry - TIMOFTE, Roxana S. (Presa Universitară Clujeană, 2019)
Assessment plays an important role in education and the teachers and academics should be aware of the different strategies used for the development of assessment tasks. Herein are presented assessment tasks developed by using different strategies: by using a competency model and by using a learning taxonomy.